Bacterial Signal Peptides- Navigating the Journey of Proteins - Kaushik, Sharbani; He, Haoze; Dalbey, Ross E. (Frontiers in Physiology, 2022)
In 1971, Blobel proposed the first statement of the Signal Hypothesis which suggested that proteins have amino-terminal sequences that dictate their export and localization in the cell. A cytosolic binding factor was predicted, and later the protein conducting channel was discovered that was proposed in 1975 to align with the large ribosomal tunnel. The 1975 Signal Hypothesis also predicted that proteins targeted to different intracellular membranes would possess distinct signals and integral membrane proteins contained uncleaved signal sequences which initiate translocation of the polypeptide chain. This review summarizes the central role that the signal peptides play as address codes for proteins, their decisive role as targeting factors for delivery to the membrane and their function to activate the translocation machinery for export and membrane protein insertion. After shedding light on the navigation of proteins, the importance of removal of signal peptide and their degradation are addressed. Furthermore, the emerging work on signal peptidases as novel targets for antibiotic development is described.